From Prescription To Practice: A Grounded Theory Of Nurses' Decision-Making In Medical Order Implementation (The Review of Diabetic Studies, 2024)
The implementation of medical orders by clinical nurses represents a complex, multifaceted process that goes far beyond simple task execution. This study explores the decision-making processes that nurses engage in when implementing medical orders, drawing primarily on recent grounded theory research by Asadi et al. (2024). Through synthesizing findings from multiple studies, this article illuminates the contextual factors, challenges, and strategies that shape nurses’ decision-making as they translate medical orders into patient care. The analysis reveals that nurses’ implementation of medical orders occurs within a dynamic healthcare environment characterized by communication challenges, workflow interruptions, and institutional pressures. The paper concludes by proposing a theoretical framework for understanding nurses’ decision-making in medical order implementation and offering recommendations for improving this critical aspect of healthcare delivery.